Inteligencia emocional y estrés por inestabilidad laboral en la oficina técnica provincial del Registro Civíl de chimborao, período septiembre 2015- febrero-2016. - Heredia Vela, María José (2016)
The topic of the present research work: “Emotional Intelligence and Job Stress Instability at the “Oficina Técnica Provincial de Registro Civil de Chimborazo, September 2015- February 2016 period”. Job instability is a stressor that has a high probability of occurrence as a result of current economic conditions, so its impact on the working population is in the majority. The Whole objective is: To determine the influence of Emotional Intelligence Stress on Labor Instability in the “Oficina Tecnica´s officials. The populations were 36 officials in the form of occasional services contracts, the sample was selected under the criteria of inclusion and exclusion that constitutes 33 officials Stress Instability Labor. The designs used were quantitative and non-experimental research type used was: field, descriptive and transversal, the level was exploratory. The techniques and instruments used were: Stress Test Instability Labor and Emotional Intelligence Test Weinsinger. Techniques for the analysis of the results were performed using basic statistics in the Excel program. The results were that 92% of the population have Instability Stress Labor, 88% has a low level of emotional intelligence. Upon completion of the research plan psychological intervention, which has a humanistic approach based on the development of emotional intelligence from the knowledge and training of emotional skills, by applying techniques and tools that help is designed to handle the Labor Instability stress.